Projeto integrado de controle de densidade e roteamento em redes de sensores sem fio - Isabela Guimaraes Siqueira (2006)
Wireless sensor networks (WSNs) are characterized by having scarce resources. The usual way of designing network functions is to consider them isolatedly a strategy which may not guarantee the correct and ecient operation of WSNs. For this reason, in this work we propose the integrated design of WSNs. We take two important WSN functions densitycontrol and routing and present two approaches for integrating them. The integration of these functions provides the reduction of the impact that density control has over routing, which is present due to topology changes caused by the alternation of the set of sensor nodes in activity. In particular, we present two solutions, named RDC-Sync and DC-Integrated, which are integrated to OGDC, a density control algorithm, and EF-Tree, a tree routing algorithm. To evaluate them, simulations experiments were performed. The results show that the integrated design improves the network performance, especially when density controland routing are fully integrated. Some of the advantages of the integrated design are: lower network trac, lower delay, energy savings, lower data loss, and better network coverage. As a result, the integrated design in WSNs is an important step towards proving improved quality of service to the applications for these networks